Training on Hand Soap Formulation Using Caesalpinia sappan (Sappanwood) - Ambarwati, Nadya; Indriani , Novamei; Vibrianita Nidom, reviany; Marfuatin Nur, Fikria; Jamaluddin Sandhori, Fajar; Purbosari, ira; Rahayu, asti; Wido Mukti, asri; Pramushinta, iak; Rifqi Prasetyawan, Hanif; rismawati (Universitas Sahid Surakarta, 2025)
: This community service aims to increase the capacity of community skills in utilizing local biological resources, especially secang wood (Caesalpinia sappan L.), as an active ingredient in making natural-based handsoap with bioactive compounds such as brazilin, tannins, and flavonoids that have antibacterial, antioxidant, and anti-inflammatory properties, as environmentally friendly hygiene products. The training will be carried out through a theoretical and practical approach, which includes the introduction of the chemical characteristics of sappang wood, active ingredient extraction techniques, natural soap formulation, production process, and equipped with basic materials for product packaging and marketing strategies, especially in the context of micro business development and promotion through digital media. From the results of the community service program about education on Handsoap Making Training Using Secang Wood, it can increase the insight and knowledge of the residents of RT Wage Sidoarjo and can improve the community's economy.